Dyadic associations between marital satisfaction and coparenting quality: gender differences and the moderating role of caregiving identity - Kuo, Patty X.; Xu, Weiman; Yang, Zhenqiao (Frontiers in Sociology, 2024)
Our study investigated the contribution of caregiving identity in the association between marital satisfaction and coparenting quality in fathers and mothers from a sample of opposite-sex couples of young children living in different areas of the United States. We conducted nested Actor-Partner Interdependence Models and moderation tests to examine potential differences between fathers and mothers in associations between marital satisfaction and coparenting quality, as well as the role of caregiving identity in the association. Results confirmed gender differences in the association between marital satisfaction and coparenting. Both mother’s and father’s caregiving identity interacted with their own marital satisfaction, but these interactions only impacted the coparenting quality reported by mothers. Additionally, caregiving identity in fathers and mothers was associated with the coparenting quality reported by their spouses. Our study highlighted the important role of caregiving identity in understanding the relation between marital satisfaction and coparenting quality in the intrafamilial processes of couples with young children.